Action, interaction and inaction: post-Kantian accounts of thinking, willing, and doing in Fichte and Schopenhauer. (2nd January 2018) - Zöller, Günter
Abstract : This article features the contributions of Fichte and Schopenhauer to a philosophical account of action against the background of Kant's earlier and influential treatment of the topic. The article first presents Kant's pertinent contributions in the areas of general epistemology and metaphysics ("transcendental philosophy"), general practical philosophy ("moral philosophy"), the philosophy of law ("doctrine of right") and ethic ("doctrine of virtues"). Then the focus is on Fichte's further original work on the issue of action in those same areas. Finally, the article turns to Schopenhauer's radical revision of the Kantian and Fichtean affirmative accounts of acting and willing through the correlated introduction of the irrational will, the self-negated will and ethical inaction.